2018
DOI: 10.1097/j.pain.0000000000001328
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic effects of a novel pH-dependent μ-opioid receptor agonist in models of neuropathic and abdominal pain

Abstract: Supplemental Digital Content is Available in the Text.The newly designed, pH-dependent opioid agonist NFEPP induced analgesia exclusively through peripheral opioid receptors in models of neuropathic and abdominal pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 43 publications
7
40
0
Order By: Relevance
“…Both fiber types express opioid receptors (44)(45)(46)(47) and transmit mechanical and heat stimuli (48,49). Consistently, exogenous opioid receptor agonists applied at the CCI site attenuated mechanical and heat hypersensitivity (40,46,(50)(51)(52). However, here we found that endogenous opioid peptides, derived from IL-4-induced M2 macrophages, attenuated mechanical but not heat hypersensitivity.…”
Section: Discussionsupporting
confidence: 77%
“…Both fiber types express opioid receptors (44)(45)(46)(47) and transmit mechanical and heat stimuli (48,49). Consistently, exogenous opioid receptor agonists applied at the CCI site attenuated mechanical and heat hypersensitivity (40,46,(50)(51)(52). However, here we found that endogenous opioid peptides, derived from IL-4-induced M2 macrophages, attenuated mechanical but not heat hypersensitivity.…”
Section: Discussionsupporting
confidence: 77%
“…Similar binding characteristics of NFEPP were recently demonstrated in homogenates of MOR-transfected human embryonic kidney (HEK) 293 cells 14 and rat brain 15 . Here, we examined mouse brain membranes by comparing the effects of NFEPP and fentanyl on the binding of the selective MOR agonist [ 3 H]-DAMGO to MOR.…”
Section: Discussionsupporting
confidence: 74%
“…Indeed, in vitro experiments confirmed that NFEPP bound to and activated μ-receptors only at acidic pH, whereas fentanyl was active at both acidic and physiological pH. Importantly, unlike fentanyl, intravenously applied NFEPP produced analgesia by activation of opioid receptors exclusively in peripheral injured tissue in rat models of unilateral hind paw inflammation or surgical incision ( Spahn et al, 2017 ), sciatic nerve injury-induced neuropathy, and abdominal pain ( Rodriguez-Gaztelumendi et al, 2018 ). Furthermore, NFEPP did not induce respiratory depression, sedation, motor impairment, reward (assessed by conditioned place preference; CPP), and constipation, even at doses 10-fold higher than the most effective analgesic doses ( Spahn et al, 2017 ) (Table 2 ).…”
Section: Targeting Opioid Receptors In Painful Tissuementioning
confidence: 98%